PENERAPAN PERPADUAN MODEL PEMBELAJARAN QUANTUM LEARNING DAN MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR DAN KREATIVITAS PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI KELAS XI LINTAS MINAT EKONOMI SMA NEGERI 1 TUMPANG - Ana Sichatul Fitria; Sapir Sapir (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2018)
This research was done in the eleventh grade of Economic Base-Interest Class at Senior High School 1 Tumpang. There were 40 students in the class which consisted of 31 females and 9 males. The data collection of the implementation of quantum learning and mind mapping was using teacher’s observation checklist. The data of the student’s learning result were obtained from pretest and postest, and the data of the student’s creativity was obtained from the observation sheet of the student’s creativity in making mind mapping.Based on the results of the data collection, there was improvement in the eleventh grade of Economic Base-Interest Class students’s learning result and creativity. This was proven by the researcher’s success on implementing quantum learning and mind mapping model. In cycle 1, 74% of the students were categorized good (B). In cycle 2, there was improvement, which was 90% of the students were categorized very good (A). It can be concluded that the student’s learning process improved from 74% in the cycle 1 to 90% in the cycle 2, or it was 19% improved. Meanwhile, the improvement of the student’s creativity in making mind mapping individually or in group was showed by the students or groups who could successfully reach the category of very good (A) in the cycle 2. At first, those students or groups could not reach that category. The success of the implementation of the learning model by the researcher was very good (A). In addition, the score of category very good (A) is 80-90. Based on the result of the study, the teachers especially the economics teachers are suggested to implement this learning especially the economics teachers are suggested to implement this learning model to improve student’s learning result and also student’s creativity. DOI: https://dx.doi.org/10.17977/UM014v11i12018p063